PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP KEPUASAN PASIEN DI INSTALASI RAWAT INAP RSUD BANGKINANG - Syamridho Rachman; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In the world of health that is in the world of nursing there is communication called therapeutic communication. This communication is very different from communication in general, because this communication is a communication that is consciously planned and its activities aim at healing the patient. One of the goals of this therapeutic communication is to get patient satisfaction. Therefore this study aims to determine the effect of therapeutic communication on patient satisfaction in the Inpatient Installation of Bangkinang District Hospital.This research method is quantitative explanation. Quantitative research requires researchers to be objective by first testing whether the boundaries of the concept and its measurement tools meet the reliability and validity standards. Meanwhile explanations are intended to explain the generalization of the sample to its population or explain the influence, differences, or influence of a variable with another. The population in this study were people who were hospitalized in Bangkinang District Hospital. The sampling technique in this study used probability sampling (population unknown), with 97 respondents. Data collection techniques in this study used a questionnaire and documentation. The data in this study were measured on a Likert scale. Data analysis performed was descriptive analysis.Based on the research results obtained significance value (sig.) Of 0,000 less than the probability of 0.05, so it can be concluded that H0 is rejected and Ha is accepted, which means there is a significant effect between Therapeutic Communication (X) on Patient Satisfaction (Y) in the Installation Inpatient at Bangkinang District Hospital. Meanwhile based on the coefficient of determination test the coefficient of determination (R2) of 0.503 was obtained. This means that the independent variable (Therapeutic Communication) has a proportion of influence of 50.3% on the dependent variable (patient satisfaction). Thus it can be concluded that the effect of therapeutic communication on patient satisfaction in the Inpatient Installation of Bangkinang District Hospital is 50.3%.